2012
DOI: 10.1183/09031936.00173411
|View full text |Cite
|
Sign up to set email alerts
|

The effect of montelukast on respiratory symptoms and lung function in wheezy infants

Abstract: Our aim was to investigate the effectiveness of montelukast in recurrently wheezy infants.We randomised 113, 6-24-month-old children with recurrent wheezing to receive either placebo or montelukast daily for an 8-week period. The primary end-point was symptom-free days. The secondary aims were to evaluate the effect of montelukast on rescue medication, on lung function, airway responsiveness and exhaled nitric oxide fraction (FeNO). Clinical response and FeNO were determined, the functional residual capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
16
0
2
Order By: Relevance
“…Infant lung function testing has been used to define phenotypes in infants with wheeze and to predict treatment effects and prognosis [120,121,[123][124][125]; several studies have tracked lung function from infancy to school age [115-117, 119, 126-131]. However, at present there is no data to support the clinical use of infant lung function tests for monitoring wheezing infants.…”
Section: Infant Lung Functionmentioning
confidence: 96%
“…Infant lung function testing has been used to define phenotypes in infants with wheeze and to predict treatment effects and prognosis [120,121,[123][124][125]; several studies have tracked lung function from infancy to school age [115-117, 119, 126-131]. However, at present there is no data to support the clinical use of infant lung function tests for monitoring wheezing infants.…”
Section: Infant Lung Functionmentioning
confidence: 96%
“…Reduced lung function in infancy was associated with respiratory morbidity and treatment needs at preschool age [65]. Some studies showed improvement of lung function, such as forced expiratory volume in 0.5 s, in infants with recurrent wheezing after ICS treatment or oral treatment with montelukast, whereas others did not show significant changes [63,64,74,75].…”
Section: Infant Lung Functionmentioning
confidence: 99%
“…Initially, Bisgaard et al conducted a randomized, double‐blinded study of children aged 3‐36 months in the post‐infectious period of RSV bronchiolitis and found that the proportion of symptom‐free infants was significantly higher for the montelukast than for the placebo group during a 28‐day treatment period (22% vs 4%, respectively). However, a large multicenter and long‐term study by the same team and a double‐blinded, randomized controlled study, failed to replicate these findings. Our findings are consistent with a recent meta‐analysis and a Cochrane review that found no effect of montelukast treatment on SFD, or the need for corticosteroids and recurrence of wheezing episodes compared with placebo for children aged less than 2 with post‐bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%